Audit Committee, Ceo Tenure And Capital Structure (Economic and Bussiness Faculty, Dr Soetomo University, 2020)
The purpose of this paper is to examine the relation between corporate governance and capital structure with moderation effect of CEO tenure in manufacturing firms listed on the Indonesia Stock Exchange. The data is acquired from the firm's annual report published in the 2013-2017 period uses multiple linear regression model and moderated regression analysis. The dependent variable in this research is capital structure measured by ratio of total debt to total assets. Independent variables used corporate governance which is measured by audit committees while moderating variable is CEO tenure. The novelty of this research examines CEO tenure as moderation variables on the influence of audit committees on capital structure which is rarely studied. The results showed that CEO tenure weakens the positive effect of audit committees on capital structure. The results of this study can help the firms to pay attention to the corporate governance and CEO tenure because they can affect the firm’s capital structure policy.Keywords - Capital Structure; Corporate Governance; Audit Committee; CEO Tenure